2017
DOI: 10.1590/1981-86372017000100003243
|View full text |Cite
|
Sign up to set email alerts
|

Simple bone cyst in a 7-year-old child

Abstract: RESUMOO cisto ósseo simples, ou cisto ósseo traumático, solitário ou cavidade óssea idiopática é um pseudocisto intra-ósseo descoberto através de um exame radiográfico panorâmico. Comumente, o cisto ósseo simples se apresenta como uma lesão assintomática, radiolúcida, unilocular, sem expansão de corticais, com margens festonando as raízes dentárias vitais da região afetada. A literatura tem recomendado que os aspectos clínicos e radiográficos do cisto ósseo simples são bastante convincentes do seu diagnóstico,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Curettage is known as an incomplete form of treatment since it frequently results in recurrence, particularly when the position of the lesion precludes a complete operation and there are concerns from medical professionals regarding the nerves around the cyst. Further, several authors have found success using CT to guide the procedure due to its size and position, ensuring clear margins, limiting nerve or microvascular injury, and yet building a 3D model for the costochondral graft (15,18). It is possible to see the vascular components of the ABC with advanced imaging tests like MRI, ultrasound, and angiography, after which one can select less invasive procedures like embolization or even more cutting-edge ones like bone marrow injection.…”
Section: Discussionmentioning
confidence: 99%
“…Curettage is known as an incomplete form of treatment since it frequently results in recurrence, particularly when the position of the lesion precludes a complete operation and there are concerns from medical professionals regarding the nerves around the cyst. Further, several authors have found success using CT to guide the procedure due to its size and position, ensuring clear margins, limiting nerve or microvascular injury, and yet building a 3D model for the costochondral graft (15,18). It is possible to see the vascular components of the ABC with advanced imaging tests like MRI, ultrasound, and angiography, after which one can select less invasive procedures like embolization or even more cutting-edge ones like bone marrow injection.…”
Section: Discussionmentioning
confidence: 99%
“…A lesão em questão neste relato apresentou características clínicas comuns ao COS, como localização em corpo mandibular e discreto o adelgaçamento da cortical óssea (expansão óssea) e dentes adjacentes a lesão com vitalidade pulpar 6,[12][13][14] . Porém, radiograficamente apresentou aparência multilocular divergindo da literatura.…”
Section: Discussionunclassified